Primary Diffuse Large B-cell Lymphoma of the Breast: Treatment and Long-Term Outcome of Two Cases - Kashyap, Rajesh; Kumar, Pradeep; Lal, Hira; Rao, Ram Naval (Indian Journal of Medical and Paediatric Oncology, 2020)
Primary breast lymphoma (PBL) is a rare form of extranodal non-Hodgkin’s lymphoma (NHL). It accounts for <0.5% of all breast malignancies and 2% extranodal NHL. Diffuse large B-cell lymphoma (DLBCL) is the most common histological subtype. We report three cases of PBL diagnosed and treated at our center. The clinical records of three female patients diagnosed with PBL from 2004 to 2015 were reviewed. Two patients had DLBCL, and the third patient had anaplastic large cell (ALCL) NHL. The mean age at presentation was 56 years. One patient with DLBCL was treated with cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) chemotherapy and the second patient with rituximab plus CHOP chemotherapy. Both the patients showed complete response and have had a disease-free survival of 84 and 96 months, respectively. The third patient with ALCL refused further treatment after confirmation of diagnosis. PBL-DLBCL can be successful treated with chemotherapy, and long-term survival is similar to nodal NHL.
Keywords: Breast lymphoma; chemotherapy; diffuse large b-cell lymphoma; rituximab